Bacteriological tests of Drinkable Water - Αρταβάνης Σπ.; Τσουτσάνης Κ.; Θεοδοσοπούλου - Τσομπανίδου Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Bacteriological tests were made in 1110 samples of drinkable water which came from recognizable municipal and parish networks of water supply, cisterns, tanks, drillings, sources, wells and slaughter-housew, tecnicalhouse technical-handicraft installations of Achia’s countfy. The tests were made at the Veterinary Laboratory of Patras and they deal with: the measurment of the bottom bacillus index per 100cm3 and the number of the total microbic flora of the middle leafs in 1cm3, the enteric streprococcus in 50cm3, the research of the Esc. Coli in 1cm3 and the Salmonella- Sigella in 20cm3. From the samples, 476 (42%) were found with bottom bucillus index more than 2/ 100cm3 and so they are unsuitable. It was also found in 490 samples (44,2%) Esc. Coli, in 93 samples (8.4%) enteric streprococcus and one sample was with S. enteritidis (0.1%) which came from slaughter-houe technical installations. Finally it is reminded the sanitary application (frequent cleaning, systematic chlorination e.t.c) to all supply and storage space carriers of drinkable water and specially to wells which have increase bottom bacillus index in 42.9% from the total number of the measured samples.